Managing Academic Stress With a Prayer Approach from a Prayer Perspective - Susanto, Dedi; Iskandar (Yayasan pendidikan dzurriyatul Quran, 2023)
This study aims to explore and describe strategies for managing academic stress using a prayer approach. Academic stress becomes a significant challenge for individuals in the context of the educational environment. With increasing academic pressure, a holistic and integrated approach is needed to improve the well-being of students. The prayer approach was chosen as the main focus of this study because of its spiritual value and its potential to have a positive impact on the mental aspects of individuals. The basic concept of prayer as a form of worship and its potential in managing academic stress will be explored in depth. This study will discuss the concept of academic stress, factors that trigger stress, and its impact on student well-being. The prayer approach is then analyzed as a key strategy, outlining its benefits to mental wellbeing and providing practical guidance in implementing it. Through a qualitative approach, this study will present a real case study that illustrates the implementation of the prayer approach in managing academic stress. Data will be collected through in-depth interviews and participant observation. It is hoped that the results of this research will provide an in-depth view of the potential of the prayer approach as a strategy for managing academic stress. Practical implications and suggestions for future research will also be discussed in this study. This study can be an important contribution in the context of understanding and managing academic stress, especially through the lens of the prayer approach